Effects of Mn additions on microstructure and properties of Fe–TiB2 based high modulus steels. (5th December 2016) - Baron, C.; Springer, H.; Raabe, D.
Abstract: We studied the effects of Mn additions from 0 to 30 wt.% on microstructure, mechanical and physical properties of liquid metallurgy synthesised high modulus steels in hypo- and hyper-eutectic TiB2 concentrations. While Mn has little effect on density, both Young's modulus and mechanical properties were strongly affected by the achieved wide spectrum of matrix microstructures, ranging from ferrite to martensite, reverted austenite, ε-martensite and austenite. Mn additions of 20 and 30 wt.% did not translate into enhanced mechanical performance despite the higher inherent ductility of the predominantly austenitic matrix, and instead eliminate the intended weight saving potential by significantly reducing the Young's modulus. Martensitic matrices of Mn concentrations of 10 wt.%, on the other hand, are favourable for improved matrix/particle co-deformation without sacrificing too much of the composites' stiffness. In hypo-eutectic Fe – TiB2 based steels, mechanical properties on the level of high strength dual phase steels could be achieved (~ 900 MPa UTS and 20% tensile elongation) but with an enhanced Young's modulus of 217 GPa and reduced density of 7460 kg m − 3 . These significantly improved physical and mechanical properties render Mn alloyed high modulus steels promising candidate materials for next generation lightweight structural applications. Graphical abstract: Highlights: Additions of 0–30 wt.% Mn to Fe – TiB2 high modulus steels result in broad spectrum of matrix microstructures Mn has little effect on density, but both Young's modulus and mechanical properties are strongly affected 20 and 30 wt.% Mn yield in γ and ε-martensite, and no gain in lightweight performance αʹ martensite and reverted γ with 10 wt.% Mn strikes an optimum balance between physical and mechanical performance